Impact Assessment of Coal Mining on Ground and Surface Water in Korba Coalfield Region, Chhattisgarh, India - Dheeraj, Vijayendra Pratap (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Mining Engineering